Inscrições Rupestres, Cantos Sagrados, Narrativas E Literatura Indígena (PERcursos Linguísticos, 2023)
I defend the recognition of indigenous sacred chants and mythic narratives as a part of Aboriginal Literature and its inclusion, in future, in Brazilian Literature. The defense is a result of ten-year research  on indigenous languages and cultures. I call the attention to two petroglyphs, a mythic narrative and a sacred chant, and to the fact that American anthropologist Robin Wright uses the expression. “Mythscapes” referring to such a heterogeneous reality present in Upper Rio Negro, Brazil. I also discuss questions related to speech, to writing and to orality.
Keywords: literature; Poetics; sacred chants; mythic narratives